Perspectives on South-South relations: China's presence in Africa. Issue 1 (2nd January 2016) - Moyo, Sam
ABSTRACT: This paper explores the broad questions on China's presence in Africa from the perspectives on South-South relations. More generally, China has a diffuse and growing presence in Africa through trade relations, as the importation of various consumer goods is highly visible in most African capital cities, and numerous smaller towns. The racial problem is compounded by the prevalence of a sinophobic media in which a racial hierarchy constructs the China below whites, albeit with blacks being relegated to the bottom. Yet there are empirically observable racist tendencies amongst the Chinese settlers towards Africans, although this is often overstated. China has become influential in Africa at the level of trade, investments and geo-political relations, but it is far from being a hegemonic recolonizer. Moreover, Africa is increasingly militarized, but China is not substantially engaged at this level. The paper concludes by suggest that much more research is necessary in the future in terms of understanding South-South international relations, so that many more people learn more about countries in the Global South and their complex set of interactions. This requires various African intellectual networks to re-visit the Bandung spirit and reconstruct the idea of non-alignment and solidarity.